2005
DOI: 10.1016/j.sigm.2005.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sensitivity: A Neurobiological Phenomenon?

Abstract: Researchers often use the term "sensitivity " when theorizing that certain persons may be more readily affected by various influences than others. Through a review of the literature, it is argued that some individuals are disposed toward a range of sensitivities that, in novelty as well as intensity, distinguish them from the general population. The author cites evidence indicating that such persons exhibit greater susceptibility to a range of environmental factors including allergies, migraine headache, chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…A parallel literature in humans (Aron, 1996;Boyce and Ellis, 2005;Jawer, 2005) notes that variation in sensitivity might be associated with variation in habitat and job choice (highly sensitive people avoid highly stimulating situations), in fine-scale behavior (e.g., preferred volume level while listening to music), in other aspects of personality (e.g., creativity), and in mental and physical well-being (e.g., extreme sensitivity might be associated with depression, migraine headaches, and suppressed immune systems).…”
Section: A Environmental and Social Sensitivitymentioning
confidence: 99%
“…A parallel literature in humans (Aron, 1996;Boyce and Ellis, 2005;Jawer, 2005) notes that variation in sensitivity might be associated with variation in habitat and job choice (highly sensitive people avoid highly stimulating situations), in fine-scale behavior (e.g., preferred volume level while listening to music), in other aspects of personality (e.g., creativity), and in mental and physical well-being (e.g., extreme sensitivity might be associated with depression, migraine headaches, and suppressed immune systems).…”
Section: A Environmental and Social Sensitivitymentioning
confidence: 99%
“…Since the negative impact of a VHFS/US sound exposure on human health is only superficially investigated and understood at the moment, the application of the precautionary principle [24] is warranted, making it necessary to regulate the use of VHFS/US sound in public places (including workplaces) more strictly to minimise potential effects on sufferers. This precaution would especially protect people that are sensitive to VHFS/US sound exposures like those with the ability to hear VHFS/US sound [21] (children being especially relevant with this respect) as well as those Highly Sensitive People (HSP) who have a lower threshold for the detection of sensory signals and have a different processing of them [25][26][27][28].…”
Section: Discussion Conclusion and Outlookmentioning
confidence: 99%
“…Aron et al (2012) have suggested that, compared with those who are less sensitive, highly sensitive individuals could also have more highly developed unconscious processing abilities and intuition, as well as more meaningful dreams and increased suggestibility (Aron et al, 2012). This was also elaborated by Jawer (2005), who discussed sensitivity from the perspective of different conceptualizations, which he suggested overlapped with SPS and indicated a shared common ground in neurobiology. One aspect of sensitivity highlighted in these conceptualizations was the tendency for the sensitive person to merge with experience.…”
mentioning
confidence: 85%
“…In comparison with less sensitive individuals, highly sensitive individuals are characterized by exhibiting more inhibition of behavior, especially in novel situations, giving them a more reflective response style; by being more sensitive to sensory stimuli, making them more prone to notice subtleties, but also increasing their risk for overstimulation; by processing information at a deeper level, giving them a complex and rich inner life; and by being more reactive emotionally, both positively and negatively (Aron, Aron, & Jagiellowicz, 2012). In earlier studies these individuals, as defined using the HSPS, have also been shown to be more sensitive to pain, medications, caffeine, and to have a higher rate of somatic problems, like migraine, headaches, chronic pain, and chronic fatigue (Jawer, 2005), as well a psychological problems, such as anxiety, depression, and social phobia (Neal, Edelmann, & Glachan, 2002).…”
mentioning
confidence: 98%